Improving agarics usability and sampling in conservation assessments - Romano, Gonzalo Matías (2023)
Species are not equally detectable, and this should be considered at the moment of choosing ecological indicators and considering sampling efforts. Indices that permit ranking gilled species according to their abundance, permanency and basidiome features were constructed. The same indices were used to evaluate sampling effort and efficiency: more than two hours of continuous work negatively affects the capability of finding less detectable species. Ranking species is a practical solution to organize abundance datasets and can be easily applied to find patterns of species relevance and detectability to better understand our findings and even to ensure optimum fieldwork efficiency.